Probiotics – a sword or a shield in COVID-19 outcome? (Research, Society and Development, 2022)
How extensively frenzy could a viral infection cause? The virus of the betacoronavirus family, SARS-CoV-2, agent of COVID-19, has shaken economic and health structures around the world since the end of 2019. There are several attempts to prevent the spread of this virus, from effective sanitary measures, or the "gold rush" for drug repositioning, to the accelerated development of vaccines. In this sense, the empirical use of antibiotics has increased even more in hospitalized patients to avoid bacterial coinfections, which could be an aggravating factor in unfavorable clinical outcomes. However, the non-rational use of these drugs, in addition to contributing to the emergence of multidrug-resistant microorganisms, can contribute to a worrying situation, intestinal dysbiosis, an event with "pleiotropic" proportions, which can significantly worsen SARS- CoV-2. Different studies report that hospitalized patients with COVID-19 have shown a reduction in the population of probiotic butyrate-producing bacteria, such as Faecalibacterium prausnitzii, in addition to a reduction in the Firmicute/Bacteroidetes ratio and an increase in the proportion of Actinobacteria, among other opportunistic pathogens. This imbalance in the gut microbiota has been correlated with increased pro-inflammatory biochemical indicators and reduced anti-inflammatory drugs, which contribute to unfavorable outcomes. Thus, understanding the harmonic and disharmonious microbial interactions in the context of COVID-19 can help develop non-pharmacological strategies capable of modulating the host response and avoiding complications, particularly concerning patients with comorbidities.